An Experiment to Test a New Theory in Physics, Fundamentally Different from General Relativity, By Changing the Speed of Light in Electromagnetic Interaction (Global Journal of Science Frontier Research, 2024)
Abstract not found
Keywords: quantum physics; general relativity; gravitational redshift; black holes; dark matter